PWE-072 Long-term outcome of endoscopic dilatation in patients with crohn's anastomotic strictures is affected by disease activity and medical therapy. (22nd June 2015) - Ding, N; Yip, WM; Saunders, B; Thomas-Gibson, S; Humphries, A; Hart, A
Abstract : Introduction: A clinically relevant stricture is usually defined as a luminal narrowing with pre-stenotic dilatation and obstructive symptoms. Surgical resection is an effective treatment for Crohn's anastomotic strictures, however disease recurrence after 15 years is more than 50%, often with the need for a further resection. 1 The long-term outcome of endoscopic balloon dilatation is unclear as most cohorts have a follow-up time of less than 3 years. Method: All endoscopic balloon dilatations performed at a single centre for patients with anastomotic Crohn's strictures between 2004–2009 were retrospectively reviewed with the aim of collecting long-term follow up data. The stricture length, signs of disease activity and evidence of upstream dilatation were assessed from imaging. Clinical data on medical therapy and escalation to anti-TNF or thiopurines was obtained. Endoscopic data including disease activity, balloon size and therapeutic success, along with histological reports were recorded. Results: A total of 54 patients were identified with a median age of 52 years (46–62). The median follow-up period was 6.48 years (5.34–7.42) with a disease duration of 28 years (19–32). Stricture length at cross-sectional imaging was described in all cases with a median of 20 mm (10–30) with features of active mucosal inflammation at the anastomosis in 38/54(70%) and upstream dilatation in 25/54(46%). At the time of endoscopy, active disease was described in 37/54(68%) of cases, a median balloon dilatation of 15 mmHg was used to achieve therapeutic success in 48/54 (89%). 10/54(18%) subsequently required surgical resection. The median number of dilatations was 2(1–9) with a time to repeat dilatation of 23 months (7.2–56.9) with 31/44 (70%) of patients being managed endoscopically requiring repeat dilatations. There was one perforation which resulted in a resection of the anastomosis and temporary ileostomy. Active disease at time of first endoscopy (p = 0.049) and stricture length >20 mm (p = 0.015) predicted need for repeat dilatations (Table 1 ). Furthermore, escalation of medical therapy to either azathioprine or anti-TNF appeared to delay time to further dilatation. Conclusion: At long term follow-up, 18% of patients required surgical resection. 32% of patients were well with no further endoscopic intervention required. 68% required intercurrent endoscopic dilatations. This is the longest follow-up period in the literature and demonstrates that the effects can be durable if patients have escalation in medical therapy to thiopurine or anti-TNF and avoidance of surgery is possible in a group of patients with anastomotic strictures. Disclosure of interest: None Declared. Reference: Predictability of the postoperative course of CD. Gastroent. 1990;99:956